Analisis Pengaruh Static Synchronous Series Compensator Terhadap Kestabilan Transien Menggunakan Metode Nyquist - Mohammad Noor Hidayat; Syarifatul Izza; Ratna Ika Putri (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2020)
Loss of synchronization causes a generator not in steady state condition, causing system instability. In this paper, Nyquist method is used to determine the transient stability of a synchronous generator using the Nyquist curve. The system is unstable if the G(jω) curve is further away from the point -1 + j0, while the gain margin value is below 6 dB and the phase margin has a value below 30°. The response of the system shows that the rotor angle oscillation on the generator is not synchronous, while the power angle experiences irregular transients so that the power angle increases until it cannot return to its steady state position. By using the Static Series Synchronous Compensator (SSSC) filter, the rotor angle oscillation response after 0.1 seconds begins to stabilize at an angle of 50°. The effect of the SSSC filter also affects the bus voltage oscillations from 0.15 seconds to 0.05 seconds and the real power oscillations from 0.13 seconds to 0.06 seconds.